2002
DOI: 10.1253/circj.66.511
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nitric Oxide Production in Response to Carbachol Between Macrovascular and Microvascular Cardiac Endothelial Cells.

Abstract: t is now established that the vascular endothelium plays a pivotal role in the regulation of blood vessel tone through the release of chemical mediators such as nitric oxide (NO). 1 Because endothelium-dependent NOmediated vasodilation can be assessed by acetylcholine (ACh) or other muscarinic receptor agonists, a number of studies have used regional infusion of ACh and examined the resultant vasodilatation. 2,3 On the assumption that a diminished vasodilator response to ACh reflects endothelial dysfunction, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Cultured HUVECs, however, do not express V2R and do not respond to DDAVP, but lung microvascular endothelial cells do express V2R and secrete vWF [38]. Nitric oxide expression is also considered to differ between microvascular and macrovascular endothelial cells [39]. Grafe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cultured HUVECs, however, do not express V2R and do not respond to DDAVP, but lung microvascular endothelial cells do express V2R and secrete vWF [38]. Nitric oxide expression is also considered to differ between microvascular and macrovascular endothelial cells [39]. Grafe et al .…”
Section: Discussionmentioning
confidence: 99%
“…A transwell insert of 0.45 micrometers (Merck‐Millipore, Darmstadt, Germany, http://www.emdmillipore.com) was added in each well, in which 5 × 10 6 bone marrow cells in Dulbecco's modified Iscove's medium (Life Technologies, Carlsbad, CA, http://www.lifetechnologies.com) were placed. To induce NO • production, endothelial cells were stimulated with carbachol (CCh, Sigma‐Aldrich, St. Louis, MO, http://www.sigmaaldrich.com) , which diffused through the medium reaching the hematopoietic cells in suspension in the transwell insert. As control, hematopoietic cells were stimulated with CCh in the absence of endothelial cells monolayer.…”
Section: Methodsmentioning
confidence: 99%
“…83 The role of the parasympathetic innervation in the coronary microcirculation is debatable, even though activation of vascular endothelial M 3 receptors results in increased NO synthesis and subsequent vasodilation. 84 Impaired autonomic function resulting in vasoconstriction is associated to CMD after AMI and/or coronary reperfusion procedures. In this regards, an early study showed that left ventricular dysfunction (secondary to transient PCI-induced ischaemia) accompanied by increased coronary resistance and diffuse vasoconstriction was abolished by a-blockers, supporting the hypothesis that neural mechanisms elicit microvascular dysfunction.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%